Effects of NaCl Stress on Callus Proliferation and Plant Regeneration from Mature Embryos of Bread Wheat (Triticum aestivum L.) Cultivars Mahon Demias and Hidhab (Plant Tissue Culture and Biotechnology, 2008)
An in vitro experiment with two cultivars, Mahon Demias and Hidhab of bread wheat (Triticum aestivum L.) exhibited appreciable callus induction but differed significantly in the capacity of calli proliferation and regeneration under salinity stress; even though Mahon Demias appeared relatively more tolerant than Hidhab. The results indicated the need to optimize a robust protocol for callus induction, maintenance and regeneration before selection process for tolerance to salinity is embarked upon.Key words: Bread wheat, Salinity stress, Callus proliferation, Mature embryoDOI = 10.3329/ptcb.v17i1.1117Plant Tissue Cult. & Biotech. 17(1): 19-27, 2007 (June)